(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Lung cancer is increasingly being detected early, and surgical treatment has a very high survival rate of over 5 years. However, there are still some recurrences after surgery, leading to changes in treatment strategies before and after surgery. In addition to chemotherapy, there are also immunotherapy methods and tyrosine kinase inhibitors. In particular, EGFR mutation testing plays an important role in providing treatment strategies before and after surgery. Objective: Evaluate gene mutation testing in adenocarcinoma lung cancer patients treated surgically at the National Lung Hospital. Subjects and methods: Lung cancer patients diagnosed by histopathology. In which, EGFR gene mutations were determined using Viennalab’s Strip Assay method from biopsy or surgical specimens at the Department of Pathology of the National Lung Hospital. Results: 40 patients were tested for EGFR gene mutations. Among them, 24/40 patients were EGFR positive. 9 patients are positive on Exon 19, 15 patients are positive on Exon 21 Conclusion: From the above results, it shows that EGFR mutation testing in lung cancer patients and the possibility of surgery is a factor in assessing prognosis and providing treatment possibilities before and after surgery.